Saberes e fazeres Javaé: estudo das práticas tradicionais alimentares indígenas, da década de 1990 a 2020 - Pereira, Tamiris Maia Gonçalves (2020)
The presente thesis objective is to discuss eating practices and habits as cultural tradition for the Javaé indigenous people, inhabitant of Bananal Island, in brazilian state of Tocantins. The main objective is to analyze and understand their eating practices, from the 1990s to 2020. The chosen time frame follows the moment when the theoretical and methodological approaches of the social sciences came to perceive the relations of power and subordination through the proposals of critical interculturality and decoloniality. The time frame also follows the moment of greatest increase of productions related to Studies of Food and History of Food. To carry out the research, bibliographic data, imagery and oral information obtained through conversations with indigenous Javaé were used. We investigated under which circumstances the denomination “traditional food” arises for this people and what were their epistemological conceptions around it. In addition, we seek to discuss the social struggles for the recognition and respect for their lifestyle and eating practices, which went through various processes of subordination during colonization. In this sense, food research allows Javaé indigenous knowledge and practices to be legitimized and valued by Brazilian national culture.